Potential for a New Multimillennial Tree-Ring Chronology from Subfossil Balkan River Oaks - Pearson, Charlotte L. (Array, 2014)
A total of 272 oak (Quercus sp.) samples have been collected from large subfossil trees dredged from sediment deposited by the Sava and various tributary rivers in the Zagreb region of northwestern Croatia, and in northern Bosnia and Herzegovina. Measurement series of tree-ring widths from these samples produced 12 groups, totaling 3456 years of floating tree-ring chronologies spread through the last ca. 8000 years. This work represents the first step in creating a new, high-resolution resource for dat¬ing and paleoenvironmental reconstruction in the Balkan region and potentially a means to bridge between the floating tree-ring chronologies of the wider Mediterranean region and the continuous long chronologies from central Europe.